(untitled) (Research, Society and Development, 2021)
Most undergraduate courses in Production Engineering have modern pedagogical projects following the national engineering curriculum guidelines. However, the creation of strategies aimed at the universe of Micro and Small Business Management (MSBM) has attributes that are not always clear in the courses. This article’s central element is to identify which strands exist in the literature regarding the teaching-learning of the MSBM in undergraduate courses in Production Engineering. The systematic literature review resulted in 20 articles published between 2016-2021, obtained from the Coordination for the Improvement of Higher Education Personnel (CAPES)’s database. The literature review addressed the topic through the dimensions of specificities of MSBM, curriculum structure for training in the Production Engineering course, and teaching-learning of entrepreneurship. The literature review also highlights the scarcity of publications that deal with the strategies aimed at micro and small enterprises in the Pedagogical Projects of Production Engineering Courses. The proposed study can contribute to the understanding of MSBM by such courses and generate revelations that guide future research.